A scalable embryonic stem cell–based platform for efficient generation of mitochondrial DNA mutant mice - Weiwei Fan; Tae Gyu Oh; Lillian Crossley; Hunter Robbins; Mingxiao He; Yang Dai; Morgan L. Truitt; Annette R. Atkins; Michael Downes; Ronald M. Evans (Proceedings of the National Academy of Sciences, 2026)
Mitochondria are central to energy metabolism and cellular signaling, and mutations in mitochondrial DNA (mtDNA) can disrupt these processes and contribute to human disease. However, progress in defining how mtDNA variation influences adaptation, pathophysiology, and disease susceptibility has been limited by the lack of suitable animal models. Although recent base-editing approaches enable direct mtDNA modification, their low efficiency restricts the generation of diverse models reflecting human mtDNA variation. Here, we develop a scalable embryonic stem (ES) cell–based platform for efficient production of mtDNA mutant mice. Random mutagenesis using an error-prone mtDNA polymerase generates a broad spectrum of mtDNA mutations, which are transferred into ES cells via a multiplexed cybrid fusion strategy coupled with sensitive mutation detection. Optimized ES cell–embryo aggregation enables robust contribution of mtDNA mutant ES cells to host embryos, producing chimeric mice with germline transmission. Using this platform, we generate a library of 155 donor fibroblast lines carrying distinct homoplasmic single-nucleotide mtDNA mutations that produce diverse mitochondrial phenotypes, including impaired oxidative phosphorylation, increased reactive oxygen species, and altered mitochondrial membrane potential. We further generate 34 female C57BL/6 ES cell lines harboring 18 mtDNA mutations across a range of heteroplasmy levels, yielding multiple chimeric mice and achieving germline transmission for one mutation. These data reveal a strong correlation between mitochondrial function and early embryonic development, suggesting a minimal energetic threshold required for normal development. This scalable resource enables systematic investigation of mtDNA variation in physiology, adaptation, disease mechanisms, and therapeutic development.